From Speech to Text: Enhancing Descriptive Paragraph Writing with Unjuk Tutur‘s Learning Model - Sulistyo, Bambang; Anam, Samsul; Erwanto, Erwanto (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2023)
This study fills a gap in the literature by examining effectiveness of one specific speaking project named Unjuk Tutur (Show and Tell) learning model in improving the ability of seventh-grade students at SMPN 01 Simpang OKU Selatan to write descriptive paragraphs. The study used a one-group pretest-posttest design with a sample of 16 out of 119 students due to social restrictions from the government in response to COVID-19. Data was collected through a descriptive paragraph writing test, and the data was analyzed using statistical techniques. The results showed a significant improvement in students' ability to write descriptive paragraphs after using the Speaking Project learning model, with an average score increase from 66.67 on the pre-test to 78.13 on the post-test. The findings suggest that the Speaking Project learning model could be an effective tool for improving students' writing skills in descriptive paragraphs. The assessment criteria used to evaluate the students' descriptive paragraphs included vocabulary, sentence structure, and spelling. The implications of this study are significant for educators seeking to enhance students' writing abilities. The Speaking Project learning model, which focuses on simple communication skills, could be an effective approach to teaching writing skills to seventh-grade students. Moreover, the findings of this study are relevant to the wider context of Indonesian language learning in the field, where there is a lack of variety in learning methods and models. In conclusion, this study highlights the effectiveness of the Speaking Project model in improving students' descriptive writing skills in Indonesian language learning. Educators can benefit from this approach to enhance students' writing abilities.